2015
DOI: 10.1017/s0021859615000775
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cellulase addition to dairy goat diets on digestion and fermentation, milk production and fatty acid content

Abstract: SUMMARYTwenty four French Alpine goats (39 ± 2·0 kg) were individually housed in a completely randomized design and fed a basal diet containing 146 g crude protein and 356 g neutral detergent fibre (NDF)/kg in the absence (control – CTRL) or presence (CELL) of 2 ml of cellulase/kg dry matter intake (DMI) for 70 days, which included a 10-day adaptation period. The feed was offered three times daily at 07·00, 13·00 and 19·00 h, but the single daily dose of cellulase was only fed at 07·00 h. Goats were hand-milke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
(73 reference statements)
2
37
1
1
Order By: Relevance
“…The high cost of cereals and quality forages has raised the interest in using fibrous roughages in the diet of ruminants (Rojo et al 2015;. Crop production is associated with the production of a number of harvesting residues and by-products, which may have important eco-doi: 10.17221/52/2015-CJAS nomic and environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high cost of cereals and quality forages has raised the interest in using fibrous roughages in the diet of ruminants (Rojo et al 2015;. Crop production is associated with the production of a number of harvesting residues and by-products, which may have important eco-doi: 10.17221/52/2015-CJAS nomic and environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing ruminant diets with fibrolytic enzymes has been shown to improve feed utilization and animal performance (Rojo et al 2015;Morsy et al 2016). However, the effectiveness of enzymes depends upon substrate, enzyme specificity, and enzyme dose (Lara-Bueno et al 2013;Elghandour et al 2015), resulting in variable responses.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient reduction of such energy losses may be potentially used for the production of more meat and milk, rather than contributing to GHG production which impacts negatively on climate change (Eckard et al, 2010). Recently, the use of exogenous enzymes (Rojo et al, 2015) and yeast (Saccharomyces cerevisiae; SC) additives in ruminant diets has attracted considerable interest (Hassan et al, 2016). Many research studies have shown that supplementing exogenous enzymes in livestock diets improved forage quality , increase digestibility, rumen fermentation, and ruminant production (Valdes et al, 2015).…”
mentioning
confidence: 99%
“…Furthermore, some agricultural byproducts have been reported to have a low nutritional value for animals as a result of low nutrient digestibility and crude protein content, poor palatability, and high fibre content . Therefore, the efficacy of digestive utilization is reduced in the presence of those byprducts . For a better utilization of these agricultural byproducts in ruminant nutrition, an improvement of their nutritive value before feeding to an animal is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Therefore, the efficacy of digestive utilization is reduced in the presence of those byprducts. 4 For a better utilization of these agricultural byproducts in ruminant nutrition, an improvement of their nutritive value before feeding to an animal is necessary. Different strategies could be applied.…”
Section: Introductionmentioning
confidence: 99%